Pengaruh Model Pembelajaran Pemecahan Masalah Berdasarkan Gaya Belajar terhadap Motivasi dan Hasil Belajar di Kelas XI SMAN 5 Padang - Refnywidialistuti Refnywidialistuti; Mudjiran Mudjiran; Yuliani Fitri (Departement of Mathematics Education, 2022)
The learning model that has been carried out so far in class III is mostly focused on conventional teacher-centered learning that relies on lectures. This study aims to get an overview of learning outcomes and learning motivation in kinesthetic, visual and auditory styles taught by problem solving models. This study uses a quantitative method with a quasi-experimental research type. The population and sample of this research are class XI students of SMAN 5 Padang. Instruments used test. Data collection techniques using a questionnaire. Data were analyzed using SPSS 20. The results showed that . problem-solving models can motivate students in learning mathematics with heterogeneous learning styles by increasing relations and interactions between students, as well as providing opportunities for peer tutoring and mutual support. The problem-solving model is more effective when compared to conventional learning models in improving student learning outcomes in class XI SMAN 5 Padang.